The Complicated but Plain Relationship of Intellectual Disability and Well-being - Gould, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2020)
The common belief is that disability is bad for the person who is disabled, that it has a negative effect on well-being. Some disability rights activists and philosophers, however, assert that disability has little or no impact on how well a person’s life goes, that it is neutral with respect to flourishing. In recent articles Stephen Campbell and Joseph Stramondo, while rejecting both views, claim that we cannot make any broad generalizations about the effect of disability on well-being. Whether they are right about physical and sensory disabilities, I do not know, but I argue that they are wrong about intellectual disabilities (ID). A broad generalization about intellectual disabilities is justified: it always has a negative impact on quality of life, even though there is no single negative impact. The disadvantages of ID are plain (all ID is bad) but complicated (its badness depends on multidimensional influences including biological condition, social environment and personal temperament).